An Outline of English Literature - Thornley, G. C. and Roberts, Gwyneth (Longman Group Ltd, 1984)
An Outline of English Literature provides a complete survey of the English prose, poetry and drama of Great Britain and Ireland from earliest times to the 1980s. It discusses the work of major writers in their historical context, with quotations, examples and illustrations.
Keywords: Literature